A Rare Presentation of Ogilvie's Syndrome - Bargiela, I (2019)
Ogilvie's syndrome or acute colonic pseudo-obstruction is characterized by massive colon dilation in the absence of mechanical obstruction or toxic megacolon. The phenotype associated with secretory diarrhoea is rare and is related to increased potassium channel activity in the colon, inducing excessive potassium loss, with increased sensitivity to normal serum aldosterone levels. The recommended therapy is potassium-sparing agents. We present the case of an 85-year-old patient who was admitted at the emergency department with prostration, abdominal distension and diarrhoea, corresponding to functional colonic dilation precipitated by severe hypokalaemia. Resolution of the condition only occurred after spironolactone was administered for suspected primary hyperaldosteronism, which was not proved as the patient showed normal aldosterone serum levels. The pathophysiological mechanism of abnormal potassium secretion in this scenario corresponds to 'relative hyperaldosteronism' caused by increased sensitivity of colonocytes to aldosterone. LEARNING POINTS: Colonic pseudo-obstruction is not usually associated with secretory diarrhoea and severe hypokalaemia.Although serum aldosterone levels are normal, the treatment of choice is spironolactone due to its effect on the potassium channels in colonocytes.It is essential to recognize this specific phenotype so that the correct clinical approach, diagnosis and management can be established.